Academic Word List In Efl Sttudent’s Written Register - Ahmad, Karmila; Tanipu, Zulkifli; Ali, Sri Widyarti (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Academic vocabulary is essential for students to engage effectively in academic discourse. This study analyzes the extent of academic vocabulary usage among students based on Coxhead’s (2000) Academic Word List (AWL). Using a corpus-based approach, the study examines a dataset comprising 902,618 tokens to determine the coverage of AWL words in student writing. The findings reveal that students used 559 out of the 570 AWL words, demonstrating a high level of academic vocabulary coverage. To further investigate the factors influencing academic vocabulary usage, interviews were conducted with students categorized into high and low proficiency groups. High-level academic vocabulary users demonstrated stronger engagement with academic texts, benefited from structured educational support, and employed active learning strategies. Conversely, low-level users exhibited limited exposure to academic texts, lacked explicit vocabulary instruction, and relied on passive learning approaches. These findings highlight the importance of targeted pedagogical interventions to enhance students’ academic vocabulary acquisition and application.